REVIVAL OF ISLAMIC CIVILIZATION; A DIRE NEED FOR SOCIAL PEACE: AN ANALYTICAL STUDY OF ISLAMIC THEOLOGY - Dr Zuha Qaisar; Dr Muhammad Zafar Iqbal Saeedi; Dr Farhana Mehmood; Muzaffar Qadar; Dr Hafiz Hamid Ali Awan; Madiha Mumtaz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The foremost purpose of a civilization is to reform, purify, and create good morals in society. It is such a cradle in which human identity is established, there are a lot of progress avenues by adopting it. Islamic civilization is also a link in a long chain of human civilizations. It is based on five basic beliefs which are called components of faith. It is necessary to believe in one God, His angels and messengers, the heavenly books and the hereafter life. Everything that is done in it is a duty. Therefore, the belief of such persons who believe in the religion of Islam is subject to Islamic teachings. The tolerance, piety, justice and brotherhood are the basic, important and soul features of Islamic civilization .The Muslims lead the world towards humanity, love, peace and reform; but when they ignored these teachings, they become the victim of humility and down fall. Hence, the revival of Islamic civilization is a dire need for social peace.